"Laptops are better." Medical students’ perceptions of laptops versus tablets and smartphones to support their learning - Curtis, Fiona; Cranmer, Sue (Proceedings of the International Conference on Networked Learning, 2014)
In recent years there has been a shift from the expectation that students will be supporting their learning with desktop and laptop computers to the increasing use of tablet computers (Payne, Wharrad, & Watts, 2012). This move has been reflected by initiatives from universities in the US and UK that have provided medical students with tablets to support their studies (Mathis, 2011; The University of Manchester, 2013). Noting this trend and considering how tablets might better support medical students, lecturers within the medical school at Lancaster University sought to find out whether their students - who had been provided with a laptop when they began their studies - perceived that they would be better served in their medical degrees by issuing them with either a laptop or a tablet. In March-April 2013, 137 students completed an online questionnaire which included open questions in which they were also encouraged to qualify their reasons. The quantitative results showed clearly that the students wanted to retain the provision of laptops rather than receiving tablets and this view was reinforced by responses to the open questions. For example, the responses showed that the medical students had a clear preference for writing up reports on a laptop rather than on a tablet. Even so, responses to the questions suggested some limitations in how far the students understood and used the capabilities of tablet computers even amongst those who already owned a tablet and/or a smart phone. Results were surprising in light of the noted trend towards tablet provision and uptake amongst medical students and therefore warrant further consideration. Emerging findings suggest that many of the medical students do not perceive tablets as suitable devices for writing, which brings forward issues relating to the concept of affordances (Parchoma, in press) and possibly medical students’ levels of digital literacy. These and other ideas will be much further developed by the point of the conference. The paper is currently work in progress. A literature review is underway; quantitative results have been analysed and coding has just begun for the analysis of the qualitative results. The results of the study will be presented at the conference for feedback.